2010
DOI: 10.1029/2009je003441
|View full text |Cite
|
Sign up to set email alerts
|

Impact into lunar regolith inhibits high‐velocity ejection of large blocks

Abstract: [1] Our data suggest that the presence of a layer of regolith covering the lunar surface results in a portion of the high-velocity ejection phase occurring in the fine-grained regolith, reducing the population of large blocks available for ejection at high velocities. This conclusion is supported by a study of boulder distributions around 10 lunar craters. The boulder ejection velocities were calculated by applying crater ejecta scaling relations and assuming a ballistic trajectory. Regolith depths were estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…A number of studies have been made on block distributions around craters on the lunar surface (Cintala and McBride, 1994;Hutton, 1969;Moore et al, 1969;Shoemaker and Morris, 1968;Bart and Melosh, 2007, 2010a, 2010b. Moore et al (1969) found that the frequencies of rocks per unit area usually decrease with distance from a crater and, according to Surveyor statistics, frequencies of blocks around fresh lunar craters change with size, locale, and distance from the crater rim.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A number of studies have been made on block distributions around craters on the lunar surface (Cintala and McBride, 1994;Hutton, 1969;Moore et al, 1969;Shoemaker and Morris, 1968;Bart and Melosh, 2007, 2010a, 2010b. Moore et al (1969) found that the frequencies of rocks per unit area usually decrease with distance from a crater and, according to Surveyor statistics, frequencies of blocks around fresh lunar craters change with size, locale, and distance from the crater rim.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Qiao et al (2014) systematically studied the topographic, compositional, stratigraphic, and geological features in Sinus Iridum using multi-source data, i.e., the Lunar Reconnaissance Orbiter Altimeter (LOLA) and Camera (LROC), SELENE Terrain Camera (TC), Clementine ultraviolet-visible (UVVIS), and Chandrayaan-1 Moon Mineralogy Mapper (M3) data. To understand the distributions of blocky ejecta, Bart and Melosh (2007, 2010a, 2010b investigated the spatial distributions of boulders ejected from lunar impact craters. The results contributed to understanding boulder ejection velocities and the distributions of secondary craters in the Solar System.…”
Section: Introductionmentioning
confidence: 99%
“…For impact craters on Earth, the size distribution of ejecta fragments has been used to model the impact spallation processes, for example at Lonar crater (e.g., Kumar et al, 2014). The impact fragments on the lunar surface were also characterized by many workers (e.g., Shoemaker et al, 1968;Hartmann, 1969;Moore, 1971;Butler and King, 1974;Cintala and McBride, 1995;Bart and Melosh, 2007, 2010a, 2010b. The high-resolution images from Lunar Orbiter and Lunar Reconnaissance Orbiter missions provided maps of ejecta boulders in and around the lunar craters, which are important for understanding the impact spallation processes (Melosh, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers also studied the distributions of rocks and craters to better understand other geologic characteristics of the lunar surface (Bart & Melosh, 2010a;Mendell, 1976;Xiao & Strom, 2012). Xiao and Strom (2012) pointed out that a thinner regolith, which is more easily penetrated to reach bedrock during impact cratering, is likelier to result in a rockier surface.…”
mentioning
confidence: 99%
“…Xiao and Strom (2012) pointed out that a thinner regolith, which is more easily penetrated to reach bedrock during impact cratering, is likelier to result in a rockier surface. Bart and Melosh (2010a) studied the relationship between rock ejection velocity during impact cratering, and Bart and Melosh (2010b) further investigated the distribution of boulders ejected from craters. Krishna and Kumar (2016) investigated the shape and size of ejecta boulders as well as secondary craters distributed around the Censorinus crater on lunar surface.…”
mentioning
confidence: 99%